Land Use Planning for Brackish Water Shrimp Ponds in The North Coast of Tuban, Indonesia - Widiatmaka Widiatmaka; Wiwin Ambarwulan; Yudi Setiawan; Muhamad Yanuar Jarwadi Purwanto; Taryono Taryono; Hefni Effendi (Faculty of Geography, Universitas Gadjah Mada, 2015)
Shrimp is a commodity that is increasingly in demand. The limited land resources implies the need of effective land use planning. The objective of this study was to assess land suitability for brackish water shrimp ponds, which then will be recommended for pond development in the north coast of Tuban, Indonesia. Analytical hierarchy process (AHP) were used to obtain the weight of the different criteria consisted of soil characteristics, topographic, water quality, and infrastructure criteria. The suitable land for brackish water shrimp ponds was determined by weighted overlay in GIS. The results show that the study area contains highly suitable land for brackish water shrimp ponds. Land use and land cover map was interpreted from 2014 SPOT 5 imagery. The area recommended for brackish water shrimp pond wasdelineated by taking into account the suitability and the constraints of land use and land cover.